Comparison of pharmacodynamics between low dose ticagrelor and clopidogrel after loading and maintenance doses in healthy Korean subjects. (September 2015) - Guo, Long Zhe; Kim, Moo Hyun; Jin, Cai De; Lee, Ju Yeong; Yi, So Jeong; Park, Min Kyu; Cho, Young-Rak; Park, Tae-Ho
Abstract The novel antiplatelet agent ticagrelor has been demonstrated to exert a faster and more powerful inhibition of platelet aggregation in comparison to clopidogrel in coronary artery disease patients. However, a ticagrelor dose of 90 mg twice daily might not be suitable for patients of East Asian ethnicity, and has not been fully investigated. The aim of this study was to assess the effects of low loading doses (LD, 90 mg) and maintenance doses (MD, 90 mg daily) of ticagrelor in comparison to clopidogrel (600 mg LD, 75 mg daily MD) in healthy Korean volunteers. Twelve subjects were randomized into two groups, receiving either clopidogrel (600 mg LD, followed by 75 mg MD daily for 5 days) or ticagrelor (90 mg LD, followed by 90 mg MD daily for 5 days). Following a 2-week washout period, the treatments were switched between the groups. Three platelet function assessment methods which included light transmission aggregometry (LTA), the VerifyNow assay and multiple electrode platelet aggregometry (MEA) were then used to serially measure platelet function at various time points (baseline, 0.5, 2, 6, 24, 26, 120 and 122 h). The mean IPA to 10 µM ADP in the ticagrelor group was significantly higher than that for the clopidogrel group at the 0.5, 2, 6, 26 and 122 h time points (p ≤ 0.001). However, there was no significant difference between the two groups at the 24- and 120-hour time points (p > 0.05). The assay results produced by the other two platelet function tests (VerifyNow and MEA) were similar to those obtained by LTA. The low loading and maintenance doses of ticagrelor (90 mg LD, 90 mg daily MD) cause a more rapid and potent inhibition of platelet function when compared to clopidogrel (600 mg LD and 75 mg MD). Additionally, at the lowest value of platelet inhibition strength, oral once-daily administration of ticagrelor was no less efficacious than clopidogrel at the 24- and 120-hour time points. Due to a large diurnal variation occurring with a single daily dose, a lower dose twice-daily could be a better option for patients of East Asian ethnicity.